2014
DOI: 10.1080/10826068.2014.969437
|View full text |Cite
|
Sign up to set email alerts
|

Optimization, purification, and characterization of L-asparaginase fromActinomycetales bacteriumBkSoiiA

Abstract: Actinobacteria are promising source of a wide range of important enzymes, some of which are produced in industrial scale, with others yet to be harnessed. L-Asparaginase is used as an antineoplastic agent. The present work deals with the production and optimization of L-asparaginase from Actinomycetales bacterium BkSoiiA using submerged fermentation in M9 medium. Production optimization resulted in a modified M9 medium with yeast extract and fructose as carbon and nitrogen sources, respectively, at pH 8.0, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“…Halophilic enzymes have high negative charges so can be easily dissociated and become more flexible in the presence of sodium chloride (Han et al 2014). The current results agree with that of some researches (Elshafei et al 2012; Dash et al 2016; Shechtman 2013; Han et al 2014). A gradual increase in the enzyme activity was reported by increasing asparagine concentration followed by slight decrease in the activity at higher concentration.…”
Section: Discussionsupporting
confidence: 93%
“…Halophilic enzymes have high negative charges so can be easily dissociated and become more flexible in the presence of sodium chloride (Han et al 2014). The current results agree with that of some researches (Elshafei et al 2012; Dash et al 2016; Shechtman 2013; Han et al 2014). A gradual increase in the enzyme activity was reported by increasing asparagine concentration followed by slight decrease in the activity at higher concentration.…”
Section: Discussionsupporting
confidence: 93%
“…The same authors reported that negative charges are associated with halophilic enzymes and the presence of sodium chloride renders these enzymes more flexible with an increase in enzyme activity. The results reported in this study agreed those obtained by many researchers (Dash et al 2016;Elshafei et al 2012;Han et al 2014;Shechtman 2013) who reported that sodium chloride increases enzyme activity. Regarding l-asparaginase activity produced by Stenotrophomonas maltophilia test isolate in relation to asparagine concentration, it was found that this relationship obeys the commonly exhibited by various enzymes.…”
Section: Discussionsupporting
confidence: 93%
“…The Mg 2+ co-factors can activate L-asparaginases by first activating the substrate and then combining it with the complex enzyme substrate to complete the enzyme-catalyzed hydrolysis reaction [21]. In our study, Mg 2+ , Mn 2+ , and Ni 2+ played active roles in activating GmASNase, which were identical to those of the L-asparaginases from A. bacterium [49], B. amyloliquefaciens [31], T. zilligii [12], Cobetia amphilecti [51], and P. fluorescens [40]. However, divalent metals do not affect the enzymatic activity of L-asparaginase from T. kodakarensis [47].…”
Section: Discussionsupporting
confidence: 51%
“…GmASNase was quite stable at 4 to 35 • C, approximately 50% of its residual enzyme activity could be retained after 30 min at 40 • C, and a significant loss of stability was recorded with the increasing of the temperature. However, L-asparaginase from A. bacterium [49] is only stable from 4 to 10 • C. In addition, L-asparaginase from Acinetobacter soli shows poor thermostability with a half-life at 40 • C of 9.63 min [10]. These results suggest that GmASNase is thermally stable.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation